The Influence of Service Quality and Business Communication on Customer Retention at Hayujalan Tour & Event - Siti Aisyah Nurlatifah; Dani Adiatma; Stanny Dhamayanty (Jurnal Sains Terapan Pariwisata, 2026)
This study aims to analyze the influence of service quality and business communication on customer retention at Hayujalan Tour and Event as a tourism service provider. The study employs a quantitative approach using a survey method by distributing questionnaires to customers who have previously used the company’s services. The research sample consisted of 77 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression to examine the influence of independent variables on the dependent variable. The results show that service quality does not have a significant partial effect on customer retention, while business communication has a positive and significant influence on customer retention. Furthermore, the simultaneous test indicates that service quality and business communication together have a significant effect on customer retention. These findings suggest that effective business communication plays an important role in building long term relationships with customers and encouraging the continued use of tourism services. The contribution of this study highlights the importance of strengthening integrated business communication strategies alongside service quality in order to improve customer retention in the tourism service industry.